Stingless bee and its socioeconomic potential in the States of Paraíba and Rio Grande do Norte (Research, Society and Development, 2020)
Meliponiculture has great importance in family farming as it is a source of income for small producers. It is an activity in expansion throughout the national territory due to the vast diversity of flora and the most varied types of climates existing in Brazil. This potential produced reflects in the income generation of the producer and, with this, stands out as an important factor of social inclusion. In the states of Paraíba and Rio Grande do Norte, the rational breeding of stingless bees is practiced from generation to generation, however there are no precise records on investment costs and maintenance of a meliponary, nor on production costs. Given the above, the objective was to research honey producers in these two states in northeastern Brazil, to evaluate and compare the socioeconomic potential of the activity of stingless beekeeping. The research was carried out in the states of Paraíba (PB) and Rio Grande do Norte (RN) during the period from May 2017 to May 2019, with data collection involving themes related to the process of stingless beekeeping, from information provided by the creators of these two states. For this study, 45 (forty-five) honey farmers were evaluated in the four mesoregions of the State of Paraíba and Rio Grande do Norte. According to the evaluations, it can be seen that the species of stingless bees most bred in both states are Abelha Jandaíra (Melipona subnitida), Uruçu Nordestina (Melipona scutellaris), Gust (Melipona asilvae), Mandaguari (Scaptotrigona sp) and Moça White (Frieseomellita sp).